Urban Ethnobotany of Jammu: Documentation of Ethno-Medicinal Plants Used in Diabetes Management - Rishita Khajuria; Roshi Sharma; Abhishek Dutta (Archives of Current Research International, 2025)
The present investigation deals with the use of ethnomedicinal plants for diabetes management in urban areas of Jammu. Several field surveys were conducted in Jammu district from the year from 2022 to 2024, for the documentation of medicinal plant usage among local communities. The data were collected through interviews with the local inhabitants using semi-structured questionnaires. Plant species were documented, collected, identified and categorized based on their anti-diabetic properties. A total of 20 plant species spread over 19 genera and 14 families were reported having anti-diabetic ethnomedicinal uses. Among these, eight species such as Alstonia scholaris, Butea monosperma, Eucalyptus globulus, Hibiscus × rosa-sinensis, Ipomoea carnea, Kalanchoe pinnata, Monoon longifolium, and Oxalis corniculata were novel addition to the ethnobotanical knowledge of Jammu & Kashmir. The findings further highlight the urgent need for conservation efforts to safeguard both medicinal plant biodiversity and indigenous knowledge, promoting sustainable practices and integrating traditional plant-based remedies along with modern healthcare diabetes management while preserving cultural heritage.